Reliability evaluation of dynamic systems excited in time domain : alternative to random vibration and simulation /: alternative to random vibration and simulation. (2023) - Haldar, Achintya; Azizsoltani, Hamoon; Gaxiola-Camacho, J. Ramon; Vazirizade, Sayyed Mohsen; Huh, Jungwon
No abstract available